An Energy and Latency Aware WSN MAC Protocol for Bidirectional Traffic in Data Collection - Ji-Yeon Min; Sang-Hwa Chung; Yuvin Ha (International Journal of Distributed Sensor Networks)
This paper proposes a new Energy and Latency Aware MAC (ELA-MAC) protocol that provides high energy-efficiency and low latency for data collection applications in wireless sensor networks. In previous research, B-MAC+ avoids the receiver node's preamble overhearing of B-MAC with short preamble packets including only the destination address and the preamble packet number. However, like B-MAC, B-MAC+ has the sender node's preamble overhead and communication latency. XY-MAC tries to solve these problems with inserting an early ACK between preamble packets. However, with the independence of each node's wake-up point, the receiver node's idle listening duration of XY-MAC is always longer than that of B-MAC+. ELA-MAC spreads collection-request without using an early ACK and delivers collection-response using an early ACK with considering the traffic types such as broadcasting and convergecasting. In this way, energy consumption on both downlink and uplink can be reduced. Besides, the time for collecting data can be shortened on uplink. With the experimental parameter obtained by the energy consumption analysis, the experiment was performed on a real sensor network test bed with various topologies. We obtained the result that ELA-MAC improves the energy efficiency by 12% and 37% compared to B-MAC+ and XY-MAC, respectively, and data collection time by 28% compared to B-MAC+.